2018
DOI: 10.1007/s00345-018-2306-7
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary rates of adherence to international guidelines for pelvic lymph node dissection in radical cystectomy: a population-based study

Abstract: It is encouraging to note increasing rates of PLND at RC over time. Both patients and hospital characteristics influence PLND rates. More efforts should be aimed at reducing inequalities in PLND at RC due to these highly modifiable variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Perioperative chemotherapy was evenly administered in the different histologic subtypes, with patients with lymphoepitheliomalike UC (25, 65.8%), neuroendocrine tumor (250, 65.4%) and micropapillary UC (91, 51.4%) being most frequently treated with chemotherapy. The median number of removed lymph nodes ranged from 11 to 19 in all the study groups (Figure 2): patients with lymphoepithelioma-like UC had the highest number of lymph nodes removed (median 19, interquartile range [IQR]: 7-26), while patients with giant and spindle cell carcinoma had the lowest (11,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Overall Descriptive Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative chemotherapy was evenly administered in the different histologic subtypes, with patients with lymphoepitheliomalike UC (25, 65.8%), neuroendocrine tumor (250, 65.4%) and micropapillary UC (91, 51.4%) being most frequently treated with chemotherapy. The median number of removed lymph nodes ranged from 11 to 19 in all the study groups (Figure 2): patients with lymphoepithelioma-like UC had the highest number of lymph nodes removed (median 19, interquartile range [IQR]: 7-26), while patients with giant and spindle cell carcinoma had the lowest (11,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Overall Descriptive Characteristicsmentioning
confidence: 99%
“…Lymph node metastases may occur in up to one fourth of patients with muscle-invasive urothelial cancer of the bladder (MIBC) [1], and their presence is an important indicator of long-term survival and cancer recurrence [2][3][4]. Therefore, radical cystectomy with pelvic lymph node dissection (PLND) is the standard treatment for MIBC [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, adherence to these recommendations is inconsistent and suboptimal, with substantial variability in clinical practices and differences in practice patterns, costs, and outcomes ( 14 - 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of lymphadenectomy (LND) during radical cystectomy has increasingly been recognized in international guidelines [1]. Although further supportive evidence is required, an increasing number of studies have shown that the number of metastatic lymph nodes (LN) and the LN density (positive LN/total LN) are independent predictors of disease evolution [2].…”
Section: Introductionmentioning
confidence: 99%